Adsorption of Cr(VI) from aqueous solution by chemically modified natural cellulose. Issue 43 (13th September 2016) - Zhu, Hongxiang; Kong, Qiaoping; Cao, Xuejuan; He, Hui; Wang, Jin; He, Yucai
Abstract: The paper researched a novel chelating material made from natural cellulose pretreated with plasma (150 V, 120 s) for the adsorption of heavy metal ions from aqueous solutions. The first section of this paper details our study on the chemical modification of bamboo fibers pretreated with plasma containing epichlorohydrin, diethylenetriamine, and carbon disulfide. Under optimum conditions, the capacity of the bamboo adsorption material prepared with plasma to adsorb Cr(VI) ions was 32.4 mg/g. The treated materials were characterized by scanning electron microscope (SEM), X-ray diffraction (XRD), and energy-dispersive X-ray spectroscopy (EDAX). The second section of this paper tests the adsorption capacity of the bamboo material with Cr(VI) ions in an aqueous solution by the classic titration method. The Langmuir adsorption isotherm and Freundlich adsorption isotherm models both provided a good fit to the data. A kinetic study showed that the absorption of Cr(VI) ions onto the modified bamboo fibers could be adequately described by a pseudo-second-order kinetics model ( R 2 = 0.9941). The model of solid–liquid adsorption in the adsorption process was provided.